In situ testing of candidate odorant cues in coral-reef fish: a new method with tests of dimethylsulfoniopropionate and betaines - Hill, Richard W.; Florn, Aaron M.; Vermeij, Mark J. A.; Frade, Pedro R. (Frontiers in Marine Science, 2023)
In situ testing of candidate odorant cues directly in coral-reef communities has the advantage that, in principle, it permits the behavioral responses of all fish species to be evaluated in the species’ natural environments. The success of in situ testing depends critically, however, on a suitable method of odorant release. We provide here a proof-of-concept for a new method of release that (instead of using distilled water as an ejection medium) ejects odorant-containing local reef water remotely and silently over an extended time period using gravity as the motive force. The ejected water, being neutrally buoyant, remains in the reef community, dispersing in local currents. From our observations of fish behavior during ejection of candidate odorants in Curaçao reefs, we confirm that brown chromis (Chromis multilineata) are likely attracted to dimethylsulfoniopropionate (DMSP), and we obtain suggestive evidence that they are attracted to a mix of three betaines: glycine betaine, proline betaine, and trigonelline. Creole wrasse (Clepticus parrae) and yellowhead wrasse (Halichoeres garnoti) are likely repelled by DMSP. Many observed fish species gave no evidence of being affected by either DMSP or betaines.